2009
DOI: 10.1080/13557850802699155
|View full text |Cite
|
Sign up to set email alerts
|

Changes in racial/ethnic disparities in the prevalence of Type 2 diabetes by obesity level among US adults

Abstract: Objective Ethnic minority status and obesity are two independent risk factors for type 2 diabetes (T2D). There is no clear understanding of how they may have interacted and influenced disparities in T2D prevalence over time. This study examined the trends in racial/ethnic disparities in the prevalence of T2D by weight status among US adults. Methods We used nationally representative data from the National Health and Nutrition Examination Surveys (NHANES) I (1971–1975), II (1976–80), and III (1988–1994), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 47 publications
6
73
1
1
Order By: Relevance
“…2,15,16 Nationally, African American, Hispanic, American Indian/Alaska Native, and multiracial individuals, as well as people who did not speak English before entering school, have worse health literacy than white Americans and those who spoke only English prior to school. 2 Similarly, across the United States, African American, Hispanic, American Indian/Alaska Native, and Asian Americans have a higher prevalence of diabetes and its complications than white Americans, with disparities in diabetes prevalence growing over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,15,16 Nationally, African American, Hispanic, American Indian/Alaska Native, and multiracial individuals, as well as people who did not speak English before entering school, have worse health literacy than white Americans and those who spoke only English prior to school. 2 Similarly, across the United States, African American, Hispanic, American Indian/Alaska Native, and Asian Americans have a higher prevalence of diabetes and its complications than white Americans, with disparities in diabetes prevalence growing over time.…”
Section: Introductionmentioning
confidence: 99%
“…2 Similarly, across the United States, African American, Hispanic, American Indian/Alaska Native, and Asian Americans have a higher prevalence of diabetes and its complications than white Americans, with disparities in diabetes prevalence growing over time. 15,16 Several studies have also reported that both Hispanic and African American patients prefer counseling over antidepressant medication when treating affective illness, which could influence adherence to these medications. Furthermore, diabetes control is more closely linked with depression and missing medication doses among African American relative to white patients.…”
Section: Introductionmentioning
confidence: 99%
“…ABD'de yapılan NHANES araştırması 1960'lı yıllardan 2000'li yıllara, 20-74 yaş grubu erişkinlerde VKİ'nin ortalama 25 kg/m 2 'den 28 kg/m 2 'ye çıktığını göstermiştir [8]. Dünya Sağlık Örgütü (DSÖ) verilerine göre ise 2015 yılı içinde dünya nüfusunun yaklaşık %10'un obez olacağı tahmin edilmektedir [9].…”
Section: Introductionunclassified
“…The role of epigenetic and environmental factors in type 2 diabetes has long been known (e.g., Zhang et al, 2009;Wallach and Rey, 2009). Haataja et al (2008), for example, conclude that the islet in type 2 diabetes shows much in common with neuropathology in neurodegenerative diseases where interest is now focused on protein misfolding and aggregation and the diseases are now often referred to as unfolded protein diseases.…”
Section: Protein Folding Regulationmentioning
confidence: 99%